Growth Parameter and Fecundity of Fringe Scale Sardine (Sardinella fimbriata Cuvier Valenciennes) in Alas Strait, East Lombok, West Nusa Tenggara - Vindy Rilani; Mulyanto Mulyanto; Daduk Setyohadi (Journal of Experimental Life Science)
Fisheries in the Alas Strait, East Lombok, West Nusa Tenggara is one of important sea area for the activity of fishing, especially small scale fishermen. In addition, the Alas Strait have a good fishery for catching pelagic fish species of Fringe Scale Sardine (Sardinella fimbriata). The aim of this study was to asses the growth parameter and fecundity of Fringe Scale Sardine (S. fimbriata). The research was conducted on August to December 2016, at the Fish Landing Base Tanjung Luar, East Lombok, West Nusa Tenggara. Survey methods and stratification sampling method were used from commercial catch. The relation between weight and length of S. fimbriata males and females are the values of b range 2.62750-2.69449 and 2.63959-2.72040, respectively. The growth patterns of male and female fish showed negative allometric growth pattern. The growth parameters of male fish is L∞ 177.50 mm; K 0.51month-1; t0-0.53month-1, while for female fish L∞ 185.00 mm; K 0.67month-1; t0 -0.41month-1. Fecundity ranges from 2801- 60 578 eggs and diameter size range of eggs 8-67 µm.